Analisis Kepuasan Pemustaka Terhadap Kualitas Layanan Perpustakaan Kampus Berdasarkan Model LIBQUAL+ - Azzahra, Nur Sifa Azzahra; Anjani, Devita Ragil; Meiana, Indah; Hapsari, Resta Rania; Hidayatullah, Muhammad; Nugraha, Joko Tri Nugraha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze library users’ satisfaction with library service quality based on the LibQUAL+ model. The method used was a descriptive quantitative approach involving the distribution of questionnaires to 71 respondents, with analysis conducted using descriptive statistics. The results indicate that library service quality falls within the good to very good category, with the “Library as Place” dimension having the highest average score. Meanwhile, the “Information Control” and “Affect of Service” dimensions are in the good category but have not yet reached an optimal level.This situation arises because the library’s physical facilities have been well-managed, thereby providing comfort to users, whereas information access and the quality of service interactions still have limitations in fully meeting user needs. Therefore, efforts to improve service quality should focus on aspects of information access and staff service. This study serves as a foundation for library administrators to evaluate and continuously improve service quality in a manner that is more oriented toward user needs.